Histone Acetyltransferases in Plant Development and Plasticity - Boycheva, Irina; Vassileva, Valya; Iantcheva, Anelia (Current Genomics, 2014)
In eukaryotes, transcriptional regulation is determined by dynamic and reversible chromatin modifications, such as acetylation, methylation, phosphorylation, ubiquitination, glycosylation, that are essential for the processes of DNA replication, DNA-repair, recombination and gene transcription. The reversible and rapid changes in histone acetylation induce genome-wide and specific alterations in gene expression and play a key role in chromatin modification. Because of their sessile lifestyle, plants cannot escape environmental stress, and hence have evolved a number of adaptations to survive in stress surroundings. Chromatin modifications play a major role in regulating plant gene expression following abiotic and biotic stress. Plants are also able to respond to signals that affect the maintaince of genome integrity. All these factors are associated with changes in gene expression levels through modification of histone acetylation. This review focuses on the major types of genes encoding for histone acetyltransferases, their structure, function, interaction with other genes, and participation in plant responses to environmental stimuli, as well as their role in cell cycle progression. We also bring together the most recent findings on the study of the histone acetyltransferase HAC1 in the model legumes Medicago truncatula and Lotus japonicus.
Keywords: Cell cycle progression